Anticipatory Trading Against Distressed Mega Hedge Funds - Agarwal, Vikas; Aragon, George O; Nanda, Vikram; Wei, Kelsey (Review of Financial Studies, 2025)
Stocks expected to be sold by distressed mega hedge funds (MHFs) face anticipatory institutional selling and increased short interest. However, no evidence of anticipatory trading is found in stocks held by nondistressed MHFs, distressed non-MHFs, or stocks confidentially held by distressed MHFs, suggesting that public portfolio disclosure by large and closely followed distressed investors, and not common investment signals, drives anticipatory trading. Distressed MHFs with greater exposure to such anticipatory trading suffer 2.21% lower style-adjusted returns. Stocks subject to anticipatory trading experience negative abnormal returns followed by reversals, indicating the price destabilizing effect of anticipatory trading.